In vitro propagation of Cattleya Lindl. and Laelia Lindl. species - Lavrentyeva, Alla (Universidad de Costa Rica, 2015)
Nowadays many wild species of South American’s orchids are under threat of extinction from over-col- lection and habitat destruction. Many tropical native orchid species were propagated in the National Botanical Garden of National Academy of Sciences of Ukraine through a range of asymbiotic seed germi- nation techniques and tissue culture procedures aimed to preserve a number of individuals under artificial conditions in glasshouses in the temperate zone, with the aim to protect these species from complete extinc- tion. Our orchid collection includes plants of Cattleya and Laelia species. Some of these species are rare in the wild. To protect them from extinction the meth- ods of propagation should be developed.